Casos y cosas: semanario popular (Vol. 2, No. 46) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Somos libres...?, De todo un poco, ¡Esos frailes!, De tiempos ídos.., La tabaquera del general San Martín, Literatura, ¡Pecado!, Mi futura suegra, Por esos mundos de amor..., Nociones de esgrima, ¡No moje, tío César...!, Los leprosos festejados..., Correo franco y con....tranqueza, Cocinas de fierro.

ENGLISH: We are free..., A little bit of everything, Those friars, Of times gone by..., General San Martín's tobacco box, Literature, Sin, My future mother-in-law, Through those worlds of love..., Notions of fencing, Don't get wet, uncle César..., The celebrated lepers..., Frank mail and with .... tranqueza, Iron kitchens.
Cases and things: popular weekly (Vol. 2, No. 46)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas